Managing the necessary evil: Can payment methods reduce product returns (ausgezeichnet mit Best Paper Award) - Garnefeld, I.; Böhm, Eva; Feider, L. (2017 AMA Winter Academic Conference, Orlando, FL)

Service Awards: Do They Help or Harm in Case of a Service Failure? - Cramer, C.; Böhm, Eva; Eggert, A. (2017 AMA Winter Academic Conference, Orlando, FL)

Selling Value in Business Markets: Individual and Organizational Factors for Turning the Idea into Action - Terho, Harri; Eggert, Andreas; Ulaga, Wolfgang; Haas, Alexander; Böhm, Eva (Industrial Marketing Management)
Keywords: Marketing

Business service outsourcing in manufacturing firms: an event study - Eggert, Andreas; Böhm, Eva; Cramer, Christina (Journal of Service Management)
Purpose Many manufacturing firms entrust partners to provide services on their behalf. However, it is not clear whether and when firms can capture the potential value advantages of outsourcing business services. The purpose of this paper is to investigate the effects of different types of business service outsourcing on firm value. Design/methodology/approach The paper uses event study methodology to estimate the impact of business service outsourcing announcements on abnormal returns of publicly traded manufacturing companies in Europe. Findings External service outsourcing that directly affects the company’s customers leads to more favorable outcomes than internal service outsourcing. This effect is contingent on the strategic outsourcing intention, the service’s reliance on technology, and the choice of the outsourcing partner. Research limitations/implications Findings show that firm value depends critically on the service value it delivers to customers. Future research could explore further contingency variables, and investigate the role of service outsourcing networks and relationships. Practical implications The insights of this study help managers to decide why, how, and to whom they should outsource their business services, as well as how to justify their outsourcing decisions, and how to communicate them toward the financial markets. Originality/value This research sheds light on the value implications of outsourcing decisions. Two types of business service outsourcing are distinguished, namely, internal and external. Furthermore, the study enhances our understanding of a contingency perspective on service outsourcing decisions.
Keywords: Strategy and Management; Tourism; Leisure and Hospitality Management; Business; Management and Accounting (miscellaneous)

Pick and Place. Englisch für Mechatronik/Lehr-/Arbeitsbuch (3rd edition)

Training and commitment in a German manufacturing company during the post-2008 crisis: a case of internal flexicurity - Schneider, Martin; Flore, Johanna (The International Journal of Human Resource Management)

Signalling to young knowledge workers through architecture? A conjoint analysis - Radermacher, Katharina; Schneider, Martin; Iseke, Anja; Tebbe, Tobias (German Journal of Human Resource Management)

Potenzial der Unternehmensarchitektur im Rahmen des Employer Branding. - Radermacher, Katharina; Schneider, Martin (PERSONALquaterly)

Qualifizieren und binden: Betriebliche Weiterbildung während Kurzarbeit. - Schneider, Martin; Flore, Johanna (PERSONALquaterly)

Signalling to young knowledge workers through architecture? A conjoint analysis - Radermacher, Katharina; Schneider, Martin; Iseke, Anja; Tebbe, Tobias (German Journal of Human Resource Management)

The Loyalty Effect of Gift Purchases - Eggert, A.; Steinhoff, Lena; Witte, C. (2017 Winter AMA Conference Proceedings, Orlando)

Monitoring in Franchise-Netzwerken: Eine ökonomische Analyse - Breuer, Robin

Informationsasymmetrien auf dem Spendenmarkt und Möglichkeiten ihrer Reduktion: Eine Prinzipal-Agenten-Perspektive von Online Spenden - Amedick, Michaela

Pairwise versus Pointwise Ranking: A Case Study - Melnikov, Vitalik; Hüllermeier, Eyke; Kaimann, Daniel; Frick, Bernd; Gupta, Pritha (Schedae Informaticae)

Reflections on Context in Service Research. - Voss, Chris; Perks, Helen; Sousa, Rui; Witell, Lars; Wünderlich, Nancy (Journal of Service Management)
Purpose – The purpose of this paper is to examine the nature of context and its implications for theory and research in service. Design/methodology/approach – This is a conceptual paper based on exploring existing research and theory related to context in service research. Findings – The characteristics of service make context both important and challenging, there is great contextual diversity in service research as reflected, for example in ecosystems made up of multiple contextual variables. There is a need to identify the context-specific nature of middle range theory and the contextual logic of general theory. The authors explore the challenges of context for service theory and how we might learn from theory in a particular context and test or adapt it in other contexts. Originality/value – The findings of this paper are of value to researchers seeking to develop and justify theory in service research (general, middle range or theory in use).
Keywords: Research; Service theory

"Cheap Talk with Multiple Strategically Interacting Audiences: An Experimental Study" - Li, Xinyu; Peeters, Ronald ("Cheap Talk with Multiple Strategically Interacting Audiences: An Experimental Study")

Do customized service packages impede value capture in industrial markets? - Steiner, Michael; Eggert, Andreas; Ulaga, Wolfgang; Backhaus, Klaus (Journal of the Academy of marketing Science)

Understanding outcome-based contracts: benefits and risks from the buyers’ and sellers’ perspective - Boehm, Eva; Backhaus, Christof; Eggert, Andreas; Cummins, Tim (Journal of Strategic Contracting and Negotiation)

Platform adoption in system markets: The roles of preference heterogeneity and consumer expectations - Steiner, Michael; Wiegand, Nico; Eggert, Andreas; Backhaus, Klaus (International Journal of Research in Marketing)

Co-management of purchasing and marketing: Why, when and how? - Wagner, Stephan M; Eggert, Andreas (Industrial Marketing Management)